Plastic Instability in Co-Cr-Ni-Mo alloy wires drawn with different drawing practices - GVK, Sai Srikanth (2021)
Plastic instability of Co-35Ni-20Cr-10Mo alloy was studied by inflicting the material to the different drawing process, namely Full Die Drawing (FDD) and Half Die Drawing (HDD). The wires were subjected to different plastic deformations, by varying the amount of cold work (CW) reduction, and the strain hardening exponent (γ) and strain rate sensitivity (m) were determined from the logarithmic plots of the true stress and strain curves. The experimental results indicated that wires drawn with FDD practice, when compared with the HDD drawn wires, had a lower instability until 75% CW, after which it increased significantly when drawn to 95% CW. The lower instability in the FDD wires at 75% CW, was attributed to the smaller grain size, higher dislocation density and lower twin spacing which contributed to higher γ and m. Plastic strain localization because of shear band formation was noticed in the FDD 95% CW wires, which contributed to lowered ductility and increased instability in the wire due to reduced γ and m. This phenomenon was not observed in HDD wires. Therefore, the results illustrate that the drawing technique employed to process the material has a significant impact on the plastic instability of the material, with the FDD practice recommended for lower CW deformations and HDD for higher CW deformations.